Approximate Controllability Results for Second Order Neutral Impulsive Stochastic Evolution Equations of Sobolev Type with Unbounded Delay - Nirmalkumar, R.; Murugesu, R. (Journal of Applied Nonlinear Dynamics, 2026)
In this paper, we discuss the approximate controllability of the second order neutral impulsive stochastic evolution equations of Sobolev type with unbounded delay in Hilbert Spaces. A set of sufficient conditions are established for the existence and approximate controllability of the mild solutions using Krasnoselskii-Schaefer-type fixed point theorem and stochastic analysis theory. An application involving nonlinear differential equation with unbounded delay is addressed.